1987
DOI: 10.1073/pnas.84.3.663
|View full text |Cite
|
Sign up to set email alerts
|

Alternative to the steady-state method: derivation of reaction rates from first-passage times and pathway probabilities.

Abstract: An alternative method for deriving rate equations in enzyme kinetics is presented. An enzyme is followed as it moves along the various pathways allowed by the reaction scheme. The times spent in various sections of the scheme and the pathway probabilities are computed, using simple rules. (5,6): If one starts with a population of A molecules and watches their evolution, one finds (i) that for any t(Ao --Ai) = 1/(k1+ k2 + . . . + kn). [2] It is independent of the state of arrival. Note also that p = kit. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…To solve these reaction schemes analytically, we utilize Ninio's probabilistic approach 23 . Instead of calculating the concentration of a particular species as a function of time, as is traditionally performed in chemical kinetics modelling, in this approach one calculates the probability of taking a particular path along the reaction scheme.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these reaction schemes analytically, we utilize Ninio's probabilistic approach 23 . Instead of calculating the concentration of a particular species as a function of time, as is traditionally performed in chemical kinetics modelling, in this approach one calculates the probability of taking a particular path along the reaction scheme.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Here we use a probabilistic approach to provide such analytical equations 13,23 . Within this approach, the probability of taking a particular path through a reaction scheme representing the cotranslational folding of a domain can be exactly computed.…”
mentioning
confidence: 99%
“…Ninio (1987) described an alternative approach to derive kinetic expressions for enzymatic reactions. The principal idea of the Ninio approach is to track a single enzyme/template complex over time and determine its average behavior.…”
Section: Competition Between Cognate and Near-cognate Aa-trnasmentioning
confidence: 99%
“…The kinetic mechanisms and structure/function relationships of T7 DNA polymerase, KlenTaq DNA polymerase, and a Bacillus DNA polymerase which have been worked out in some detail (Johnson, 1993;Kiefer et al, 1998;Li and Waksman, 2001;Patel et al, 1991), suggested that all DNA polymerases have the same broadly conserved molecular properties and mechanisms, but that each polymerase also has unique features (Jager and Pata, 1999). Viljoen et al, (2005) and Griep et al, (2005) developed a macroscopic model of PCR kinetics which is based on the probabilistic kinetic approach described by Ninio (1987 …”
Section: Kinetics and Error Production By Polymerasementioning
confidence: 99%